The influence of debt equity ratio and times interest earned ratio through return on assets on banking companies’ share price - Sandika Utama; Bintoro Bagus Purmono; Helma Malini; Mustarudin Mustarudin; Wendy Wendy (Trigin Publisher, 2023)
The financial performance of a company significantly influences its valuation, reflected in share prices and serving as a comprehensive measure of overall health and profitability. This research delves into the intricate interplay of microeconomic and macroeconomic environments on a company's performance, focusing on the Debt Equity Ratio (DER) and Times Interest Earned (TIE) as key determinants of stock prices in banking institutions. The mediating role of Return On Assets (ROA) is considered in this analysis. Employing the multiple regression statistical method, the study aims to reveal the relationships between independent and dependent variables while accommodating intervening variables. The objective is to present empirical data supporting formulated hypotheses, providing valuable insights into the financial dynamics of banking institutions.